The power of shared philosophy: a study of midwives' perceptions of alternative birth care in Norway - Helberget, Lindis; Fylkesnes, Anne-Margrethe; Crawford, Paul; Svindseth, Marit (Mark Allen Healthcare, 2016)
Aims: The aim of this study was to explore important factors that promote the best possible health for mother and child during pregnancy, birth and post-birth in an alternative birth clinic (ABC) in Norway.